Updated recommendations of the International Society of Geriatric Oncology on prostate cancer management in older patients. (July 2019) - Boyle, H.J.; Alibhai, S.; Decoster, L.; Efstathiou, E.; Fizazi, K.; Mottet, N.; Oudard, S.; Payne, H.; Prentice, M.; Puts, M.; Aapro, M.; Droz, J.-P.
Abstract: Background: The median age of prostate cancer diagnosis is 66 years, and the median age of men who die of the disease is eighty years. The public health impact of prostate cancer is already substantial and, given the rapidly ageing world population, can only increase. In this context, the International Society of Geriatric Oncology (SIOG) Task Forces have, since 2010, been developing guidelines for the management of senior adults with prostate cancer. Material and methods: Since prostate cancer and geriatric oncology are both rapidly evolving fields, a new multidisciplinary Task Force was formed in 2018 to update SIOG recommendations, principally on health status screening tools and treatment. The task force reviewed pertinent articles published between June 2016 and June 2018 and abstracts from European Association of Urology (EAU), European Society for Medical Oncology (ESMO), American Society of Clinical Oncology (ASCO) and American Society of Clinical Oncology Genito-urinary (ASCO GU) meetings over the same period, using search terms relevant to prostate cancer, the elderly, geriatric evaluation, local treatments and advanced disease. Each member of the group proposed modifications to the previous guidelines. These were collated and circulated. The final manuscript reflects the expert consensus. Results: The 2019 consensus is that men aged 75 years and older with prostate cancer should be managed according to their individual health status, and not according to age. Based on available rapid health screening tools, geriatric evaluation and geriatric interventions, the Task Force recommends that patients are classified according to health status into three groups: (1) 'healthy' or 'fit' patients should have the same treatment options as younger patients; (2) 'vulnerable' patients are candidates for geriatric interventions which—if successful—may make it appropriate for them to receive standard treatment and (3) 'frail' patients with major impairments who should receive adapted or palliative treatment. The 2019 SIOG Task Force recommendations also discuss prospects and unmet needs for health status evaluation in everyday practice in older patients with prostate cancer. Highlights: Treatment should be based on health status evaluation and not on chronological age. Patients with impairment may benefit from a comprehensive geriatric assessment. Geriatric interventions are likely to facilitate a more appropriate and effective treatment plan. Screening for cognitive impairment is important to make treatment decisions. Introduction of palliative care should be made early in cases of metastatic disease.